Politics of Shame in Turkey: Public Shaming and Mourning - Direk, Zeynep (Sophia, 2020)
The politics of shame makes part of the politics of affects. It is becoming a prominent form of politics in the age of social media. Social media, insofar as it presents a plurality of perspectives, can be a milieu for public deliberation. Acknowledging that politics of shame can be of different types, this essay considers two different experiences of politics of shame in social media. It compares public shaming as an activist strategy of moral reform in contemporary feminist politics with politics of shame under authoritarianism by concentrating on two cases from Turkey. At first the structure of shame will be articulated by recourse to the phenomenological and psychological theories of shame. In public shaming for feminist moral reform, the publically shamed agent, who is a feminist, is accused by a group for performing an injurious speech act or a deed with mediate pernicious, harmful consequences. It is my contention that a theory of gender or sexual difference can be false, but is not morally equivalent to an attack on somebody’s existence, racism, and acts of genocide denial. Practices of public shaming in feminism are not self-defense; they are repressive and unfair attacks that destroy public deliberation. It is also problematic to attack feminists, on the grounds of arguments that are based on analogies, which do not apply to non-Western geo-political contexts. All politics of shame is not wrong. For example, the practices of politics of shame that concern non-elaborate mourning have moral and political value insofar as they can play a role in challenging an authoritarian political rule. In this case, the public shame results from attesting to injustice done to the other(s) in the public sphere, a public sphere, which is already closed, and highly manipulated by the authoritarian state.